An experimental verification of the binary method for three-phase voltage source inverter - Pang, Shen Yee (2005)
The purpose of this study is to investigate the characteristics of the Binary method through experimentation. By resolving the maximum voltage conversion factor, effect of switching frequency, harmonic elimination, total harmonic distortion and harmonics loss factor, we are able to investigate the performance of the Binary method for controlling a three-phase voltage source inverter. Both the theoretical approach and experimental work are based on a 12 -pulses per cycle binary wave. The switching angles of the 3 pulses per quadrant are obtained from the Fourier analysis and Newton-Raphson method and then transformed into time delay and stored as a look up table in PIC Microcontroller. The IGBT switches in the inverter section are triggered by the microcontroller to generate the desired output waveform. For analysis, the output voltage waveforms are analyzed using "The Output Processor" ( TOP) software. Through the experimental findings, the voltage conversion factor for Binary method is 0.92. The ideal switching frequency for the Binary method is found to be from 180Hz to 1800Hz. The Binary method shows the ability to suppress the lower order harmonic content. Also in this work, the harmonic loss factor and total harmonic distortion for different delta connected loads are investigated.